(Lack of) Pension Knowledge - Alan Barrett; Irene Mosca; Brendan J. Whelan (Institute for the Study of Labor (IZA), 2013)
Governments are increasingly concerned about the capacity of pensions systems to meet demands in the coming years. According to the OECD, one part of the policy response in many countries will be greater private provision on the part of individuals through occupational and other pension arrangements. If such a strategy is to work, it requires that individuals are well-informed about pensions. However, there are many reasons to believe that individuals may not be well-informed due to the complexity of pensions systems and degrees of myopia. In this paper, we assess levels of knowledge of pensions using a representative sample of older Irish people. Looking at people who are enrolled in pension schemes, we find that two thirds of these people do not know what amount will be paid out on retirement and/or whether the payments will be in the form of lump-sums, monthly payments or both. Women are more likely not to know, as are people with lower levels of education. While one policy conclusion might be to direct pensions-related information at certain groups, another approach might be to extend the mandatory elements in pension systems such as contribution rates.
Keywords: I38; J14; 330; pensions; knowledge; older workers